Managing the public's wildlife on private lands: a landowner's perspective - Simons, Greg, speaker; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
History of wildlife in the United States is one that witnessed remarkable recovery of many species of wildlife during the 20st century, after a major collapse during the preceding century. The North American Model of Wildlife Conservation articulates principles that reflect the basis for recovery and continued success of wildlife in the U.S., with wildlife as a public trust resource often being described as the foundation tenet of this conservation model. Public ownership of wildlife has roots which perhaps date back to ancient English and Roman common law, with such ownership premises in the U.S. dating back to 1842 where Martin v. Waddell affirmed this ownership. When considering that over 60% of land in this country is privately owned, there is potential for what some may consider a conflict in the relationship of managing and conserving the publicly owned wildlife that is found on private land. It must also be recognized that in many areas of most states, private lands stewardship is the driver of ensuring sustainable wildlife habitats on those lands. It is the author's opinion, based on observation, that incentivizing private landowners as caretakers of wildlife, should be part of this relationship equation. One component of such incentivizing should be encouraging wildlife markets, while also protecting ownership principles of public trust. Further, relationship building between private landowners and natural resource agencies is crucial in maintaining conservation success in private lands regions, and part of such relationship building is providing landowners with a regulatory framework that is friendly toward the needs and goals of those landowners, while also maintaining balance that encourages wise use of the resource.
Managing the public's resource on private lands: a landowner's perspective
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses